2019
DOI: 10.1021/acsami.9b17000
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Electrical Bistability Behaviors Observed in Au/Ag Nanoparticle-Embedded MOFs and Switching Mechanisms

Abstract: Electrically bistable devices play an important role in the next generation of information materials. Plasmonic noble metal nanoparticles (Au and Ag NPs) with diameters <6 nm were embedded into 3-D Cd-based metal–organic framework (MOF) matrixes via the photoreduction method to generate Au (Ag) NPs@MOF composites. Electrical bistability measurements on the sandwiched ITO/NPs@MOF/silver devices indicate that two switchable conductivity states with nonvolatile memory behaviors can be observed. The ITO/Au NP@2/Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…179 In 2019, Chen et al reported the synthesis of Au(Ag) NPs embedded Cdbased MOF composites (Au(Ag) NPs@MOF) by photoreduction method and the fabrication of memory devices based on Au(Ag) NPs@MOF. 180 The I-V curves indicated that the devices based on the Au(Ag)NPs@MOF composite materials showed the typical electrical hysteresis behaviors for information binary memory. Among them, the device ITO/Au NP@2/Ag (2 = {[Cd(tib)(Tdc)]Á(DMA) 3 }) has the highest I ON /I OFF current ratio of 10 4 , due to the better dispersion of Au NPs in the MOF matrix and thereby the higher electron tunneling efficiency.…”
Section: Rram Devices Based On Mofsmentioning
confidence: 96%
“…179 In 2019, Chen et al reported the synthesis of Au(Ag) NPs embedded Cdbased MOF composites (Au(Ag) NPs@MOF) by photoreduction method and the fabrication of memory devices based on Au(Ag) NPs@MOF. 180 The I-V curves indicated that the devices based on the Au(Ag)NPs@MOF composite materials showed the typical electrical hysteresis behaviors for information binary memory. Among them, the device ITO/Au NP@2/Ag (2 = {[Cd(tib)(Tdc)]Á(DMA) 3 }) has the highest I ON /I OFF current ratio of 10 4 , due to the better dispersion of Au NPs in the MOF matrix and thereby the higher electron tunneling efficiency.…”
Section: Rram Devices Based On Mofsmentioning
confidence: 96%
“…Au/Ag NPs@Cd-based MOFs films were deposited on the ITO by spin-coating, and then assembly of the ITO/NPs@ MOF film/Ag device was completed by deposition on top of Ag electrodes. 96 The NPs@MOF film-based devices displayed electrical hysteresis, presenting HRS from −5 V to −2.1 V, with a sudden increase in conductance at −2.1 V (LRS) and a return to HRS at 2.1 V, sequentially (Figure 6d). The NPs@ MOF film-based RRAM devices showed good cycling endurance, retaining switching between LRS and HRS for 200 cycles and had a high ON/OFF ratio, up to 10 4 .…”
Section: Reticular Materials Thin-film-based Resistive Switching Devicesmentioning
confidence: 99%
“…(d) I – V characteristics of the ITO/Au NPs@Cd-based MOFs/Ag device. Panels (c) and (d) are reproduced with permission from ref . Copyright American Chemical Society 2019.…”
Section: Reticular Materials Thin-film-based Resistive Switching Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The design at the molecular level, for instance, the introduction of three-dimensional nanostructures, can bring a new approach to high-density data storage for nonvolatile memories. 4,5 In typical sandwiched electrode/storage material/ electrode devices, ionic, electronic, and thermal processes are responsible for the resistive switching between the highresistance state (HRS) and low-resistance state (LRS). 6 Based on the charge trapping materials or metallic electrodes, some mechanisms have been proposed in explaining this resistance switching, including the space charge trapping, filamentary conduction, conformation change, valence change, and electrochemical metallization.…”
Section: ■ Introductionmentioning
confidence: 99%